FITTING EXTREME VALUE COPULAS WITH UNIMODAL CONVEX POLYNOMIAL REGRESSION USING BERNSTEIN POLYNOMIALS - PRADO, Danielle Gonçalves de Oliveira; CHAVES, Lucas Monteiro; SOUZA, Devanil Jaques de; EUGÊNIO FILHO, Eleanderson Campos (Brazilian Journal of Biometrics, 2022)
Bernstein polynomials are suitable for performing shape-constrained regressions, in particular, for unimodal convex regression. The Pickands function is convex and unimodal, being a fundamental element in the theory of extreme value copulas. The purpose of this article is to explain in details the use of Bernstein polynomials in the estimation of Pickands function and to establish a new test of significance for extreme value copulas.